2001
DOI: 10.1063/1.1355696
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of the vacuum ultraviolet emission and electrical characteristics of a He–Xe microdischarge

Abstract: Vacuum ultraviolet emission and electrical characteristics of a simple discharge configuration consisting of two planar cylindrical electrodes operated with a dc voltage have been measured over a wide range of He/Xe mixtures and discharge pressures. Breakdown characteristics are consistent with those found in the literature, however current–voltage characteristics and the inferred discharge resistivity suggest the presence of a complex process controlling electron emission at the cathode. Ultraviolet vacuum em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…A striking feature in the experiments is that the minimum in the discharge voltage is about the same for all mixed gas compositions studied, and equal to that measured for the pure Xe case. It is also clear that for scaled current densities above 10 -2 mA•cm -2 •Torr -2 the discharge voltages are higher than for pure xenon or pure helium, as we had seen previously 8,9 . We would expect the discharge voltage for He/Xe mixtures to be in between those of the pure Xe and pure He cases.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…A striking feature in the experiments is that the minimum in the discharge voltage is about the same for all mixed gas compositions studied, and equal to that measured for the pure Xe case. It is also clear that for scaled current densities above 10 -2 mA•cm -2 •Torr -2 the discharge voltages are higher than for pure xenon or pure helium, as we had seen previously 8,9 . We would expect the discharge voltage for He/Xe mixtures to be in between those of the pure Xe and pure He cases.…”
supporting
confidence: 76%
“…Our research aims at isolating these reactions from affects associated with complex geometries and/or non-steady fields by carrying out experiments in direct-current microdischarges of planar geometries. In recent papers 8,9 , we have presented results on the vacuum ultraviolet emission and the electrical characteristics of these planar dc microdischarges. We noted that for the range of current density studied (abnormal glow regime) the discharge voltages in mixtures of helium and xenon were surprisingly higher than in either pure xenon or pure helium, when the xenon fraction exceeded about 10%.…”
mentioning
confidence: 99%
“…Increasing the xenon content leads to an increase of the VUV production efficiency, but also to an increase of the breakdown voltage [68]. Systematic and accurate measurements of the Paschen curves [69,70] under well controlled conditions (i.e. uniform electric field, well characterized MgO layer) in a wide range of rare gas, PDP mixtures, would be very useful and are still missing.…”
Section: Gas Mixture and Uv Generationmentioning
confidence: 99%
“…The height coordinate begins at the vertex of the MD cavity and is normalized by pressure (p o ϭ600 Torr). Contour labels have units of 10 13 cm Ϫ3 and the peak electron density is noted in each frame. pd scaling qualitatively holds based on similar morphology and peak density.…”
Section: Properties Of Microdischarge Devicesmentioning
confidence: 99%
“…Early variants of MDs were constructed with the intent to operate as miniature hollow cathodes by reducing the cathode diameter while increasing the pressure to maintain the same pd as conventional low pressure hollow cathode devices. 10 Observations of optical emission spectra showed that when pd decreased into the 1-10 Torr cm range, the devices transitioned from operating similar to a Townsend discharge dominated by emission from neutral atoms to a mode resembling a hollow cathode discharge in which emission from high lying ion transitions was prominent. 1 Employing techniques developed for microelectronics and microelectromechanical systems fabrication, MD structures have been investigated.…”
Section: Introductionmentioning
confidence: 99%